Adhesive resistance of a copaiba oil-based dentin biomodifier - Maria Fulgência Costa Lima BANDEIRA; Alinne Lessa FREITAS; Manuela de Souza Cruz MENEZES; Jardel dos Santos SILVA; Gesom Avohai Dias SOMBRA; Eliane Avany Malveira ARAÚJO; Carina TODA; Ana Regina Casaroto MORESCHI; Nikeila Chacon de Oliveira CONDE (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract This study analyzed the effect of prior application of copaiba oil (CO) emulsions as a dentin cleaning substance on microleakage and microtensile adhesive strength. Twenty-five premolars and sixty-four molars were used for microleakage and microtensile assays. For the microleakage assays, specimens with standard class V cavities were divided (n = 5), according to the tested CO emulsions: CO10%X, CO10%Y, and CO10%Z, as well as chlorhexidine 2% (CHX) and distilled water (DW), as positive and negative controls, respectively. Restorations were performed using the Adper Single Bond® and/or Clearfil SE Bond® systems. Cervical, occlusal, distal and mesial sections were assessed for tracer penetration degree at the composite/tooth interface. For the microtensile assay, healthy molars were divided into sixteen groups, in which artificial caries were induced in half of the groups. Dentin surfaces were treated with CO10%X and CO10%Y, CHX and DW. Microtensile bond strength was measured by fixing each sample to the plate of a universal testing machine operated at a speed of 0.5 mm/minute until failure. Dentin treated with CO10%X showed a lower infiltration rate than dentin treated with the other CO emulsions, CHX2% and DW. According to the microtensile assay, both healthy and affected dentin treated with CO10%X and Adper Single Bond® adhesive system presented higher adhesive strength. CO emulsion, used as a dentin biomodifier, interfered positively in microleakage and improved adhesive strength after acid etching in the Adper Single Bond® adhesive system, or before applying the Clearfil SE Bond® self-etching system.